A rational design of low cost and flexible carbon composite dye sensitized solar cell. (1st June 2020) - Arbab, Alvira Ayoub; Mengal, Naveed; Memon, Anam Ali; Chul Sun, Kyung; Jeong, Sung Hoon
Abstract: Low cost carbon materials gained extensive attention in the field of sustainable energy storage devices. A major challenge in assembly of fluorine doped tin oxide (FTO) glass free dye sensitized solar cell (DSSC) is the heat treatment limitation and transparency of electrodes. In this work, a rational design of a carbon composite dye-sensitized solar cell (CC-DSSC) fabricated with stacking carbon fiber wet-laid web (CFW ) is described. The front electrode is prepared by a fibrous thin sheet of carbon fibers deposited with extended Titania nanorods (e-TiO2 nR). Whereas, the counter electrode is prepared by the composite of CF and exfoliated graphite micro platelets (Ex-GMP). The assembled CC-DSSC demonstrated 5.207% efficiency with high fill factor (FF) and open-circuit voltage (VOC ). The high VOC of designed CC-DSSC ascribed to the high transmittance (50%), sheet conductivity, and efficient charge generation of e-TiO2 nR/CFW electrode. Moreover, e-TiO2 nR provides high dye absorption and electron mobility suitable for the CFW substrate. Alternatively, high FF of CC-DSSC provides evidence of remarkable electrocatalytic activity and low charge transfer resistance (1.915 Ω) of the Ex-GMP/CFW CE system. Our proposed system of carbon composite DSSC will provide new ways towards the fabrication of sustainable and low-cost energy storage devices. Graphical abstract: Image 1 Highlights: A low-cost carbon composite dye sensitized solar cell has been fabricated. Thin transparent carbon fiber web coated with extended TiO2 nanorods used as photo anode. A composite of exfoliated graphite microplatelets and carbon fiber prepared for counter electrode. A flexible and metal free carbon composite DSSC (CC-DSSC) demonstrated 5.207% efficiency.